Freeze-all policy for in vitro fertilization in women with normal response to ovarian stimulation - Duarte-Filho,Oscar Barbosa (2021)
ABSTRACT Objective To answer the question if the freeze-all strategy and subsequent frozen embryo transfer is preferable to fresh embryo transfer for patients with normal response to ovarian stimulation (4 to 15 oocytes recovered) during in vitro fertilization treatments. Methods A retrospective cohort from two human reproduction centers between 2013 and 2017. A total of 471 frozen embryo transfers from freeze-all cycles, and 3,208 fresh transfers were included. Results After propensity score matching adjustment for age and number of eggs, 467 freeze-all cycles and 934 fresh cycles were analyzed, revealing no statistically significant difference between groups in relation to clinical pregnancy rate (32.5% in the Freeze-all Group and 32.3% in the Fresh Group, p=0.936). For women aged 40 years and older, we observed a statistically significant higher clinical pregnancy rate when freeze-all strategy was used (29.3% in the Freeze-all Group and 19.8% in the Fresh Group, p=0.04). Conclusion Freeze-all strategy was not superior to fresh transfer for all patients with normal response to ovarian stimulation. However, women aged 40 years and older could benefit from this strategy. This deserves further investigation in future research, preferable in a prospective randomized study.